Dendrophthoe falcata (L.f.) Ettingsh. and Dendrophthoe pentandra (L.) Miq.: A review of traditional medical uses, phytochemistry, pharmacology, toxicity, and applications - Kong, Degang; Wang, Lu; Niu, Yingshuo; Cheng, Lingmei; Sang, Bo; Wang, Dan; Tian, Jinli; Zhao, Wei; Liu, Xue; Chen, Yueru; Wang, Fulin; Zhou, Honglei; et al. (Frontiers in Pharmacology, 2023)
Dendrophthoe falcata (L.f.) Ettingsh. (DF) and Dendrophthoe pentandra (L.) Miq. (DP) have been traditionally used for the treatment of various ailments, such as cancer, ulcers, asthma, paralysis, skin diseases, tuberculosis, and menstrual troubles, in the ethnomedicinal systems of India and Indonesia. Currently, the chemical structures of 46 compounds have been elucidated from DF and DP, including flavonoids, triterpenes, tannins, steroids, open-chain aliphatics, benzyl derivates, and cyclic chain derivatives. In vitro assays have revealed their anti-tumor and anti-microbial activities. In vivo studies have unraveled their pharmacological properties against tumors, depression, fertility disorders, inflammatory responses, and so on. Additionally, their weak toxicity to rats and brine shrimp, as well as their promising applications for pharmaceutical preparations and combined medication, were also revealed. Herein, we not only recapitulated traditional medical uses, phytochemistry, pharmacology, toxicity, and applications of DF and DP but also discussed current research limitations and future perspectives, which are instructive for those interested in them and are committed to advancing parasitic plants to the frontier of phytomedicine. We highlighted that DF and DP will become promising medical plants rather than being discarded as notorious pests, provided that more and deeper research is undertaken.